Molecular identification of yeasts and yeast-like fungi isolates from onychomycosis cases in Medellin (Colombia) - Flórez-Muñoz, Sindy Viviana (2019)
Objective Identify yeast and yeasts-like fungal species isolated from onychomycosis cases by partial sequencing of D1/D2 from 26S rDNA region. Methods Forty-four yeast and one like-yeast isolates from patients with onychomycosis were analyzed. The D1/D2 domain of the 26S rDNA region was amplified using the NL1/NL4 primers and subsequently sequenced. Obtained sequences were aligned using CLUSTAL W and phylogenetic analysis was carried out with MEGA v7 software. Bootstrap statistical support of at least 70% was considered to group samples. Results Phylogenetic analysis allowed the identification of 13 species: Candida parapsilosis (33.0%), C. tropicalis (15.5%), C. albicans (15.5%), C. haemulonis (7.0%), C. intermedia (7.0%), C. cabralensis (4.4%), C. orthopsilosis (2.2%), C. metapsilosis (2.2%), Debaryomyces hansenii (2.2%), Meyerozyma guilliermondii (4.4%), Pichia kudriavzevii (2.2%), Trichosporon asahii (2.2%), and Wickerhamomyces onychis (2.2%). Conclusion Candida parapsilosis continues to be the most prevalent yeast as etiologic agent of onychomycosis in Colombia. In the current study, it is important to highlight the isolation of C. cabralensis, usually recognized as an environmental yeast, and W. onychis. To our best knowledge, this is the first report of an onychomycosis case caused by the former species while the latter has only been associated with a single clinical case published in 1965 as Pichia onychis.